Neurenteric Cyst of the Area Postrema - Claire M. Miller; Bonnie H. Wang; Seong-Jin Moon; Eric Chen; Huan Wang (Case Reports in Neurological Medicine)
Neurenteric cysts are CNS lesions most frequently occurring in the spinal cord. Intracranial neurenteric cysts are rarer, typically presenting with headache, mass effect, or location-specific symptoms. The area postrema is known as the emetic center of the brain; lesions can cause nausea and vomiting. Our case, featuring a neurenteric cyst of the area postrema, illustrates the importance of considering a neurological etiology for nonspecific symptoms that otherwise elude explanation. Our patient presented with acute decompensated hydrocephalus upon exploratory abdominal laparoscopy for unresolving abdominal pain. The patient had an eight-month history of unexplained intermittent nausea, vomiting, and abdominal pain. These bouts increased in frequency during the weeks before acute presentation, prompting exploratory abdominal laparoscopy. The acute decompensation was managed by ventriculostomy, and cranial MRI revealed a cystic mass by the floor of the fourth ventricle. After the patient stabilized and returned to neurological baseline, suboccipital craniectomy and resection were performed. The mass was histologically identified as a neurenteric cyst. The patient was free from neurological complaints at one-year follow-up, indicating that the successful resection of the area postrema-associated neurenteric cyst resolved her previous symptoms. Thus, some intracranial lesions can masquerade as nonspecific symptoms, presenting a challenge to accurate diagnosis.